The efficacy of pyriproxyfen-treated resting boxes on the reproductivity of Aedes aegypti (Diptera: Culicidae) in the laboratory - S. Suttana (2019)
© 2019, Malaysian Society for Parasitology. All rights reserved. Pyrethroid resistance is a problem for controlling the dengue vector Aedes aegypti worldwide. One strategy to cope with resistance is to use another insecticide with a different mode of action. Pyriproxyfen (PPF), an insect growth regulator, is normally used at very low concentrations for controlling the immature stages of mosquitoes. At high concentrations, it has a reproductive effect on exposed female mosquitoes. In this study, we demonstrated by using CDC bottle and cone bioassays that tarsal contact with 333 mg AI PPF/m2 for 1 min was sufficient to cause over 95% emergence inhibition (EI) in the progeny of exposed Ae. aegypti females. Exposure for 5 min completely inhibited fecundity. As Ae. aegypti adult mosquitoes are generally drawn towards darker areas, we evaluated the efficacy of a resting box (35x35x55 cm) treated with PPF aimed at disrupting reproductivity of free-flying mosquitoes in the laboratory. We found that the resting box led to 94% EI of exposed females, either before or after blood feeding. The resting box was also attractive for male mosquitoes. Exposed males could transfer sufficient PPF to virgin females via copulation to cause about 90% EI. Additionally, PPF-exposed gravid females from the treated resting box were able to disseminate sufficient PPF to small larvae-containing cups to reduce adult emergence by 50%. Based on 10 min exposure, the residual effect of PPF-treated resting boxes (over 80% EI) was observed over a 4 month-period. PPF-treated resting boxes may potentially be useful in dengue vector control programs, however further evaluation under natural field conditions are needed.